Clinical relevance of the sialyl-Tn antigen in bladder cancer - Santos, Ana Margarida Gonçalves (2014)
Approximately 50% of muscle invasive bladder cancers (MIBC) develop metastasis within 5 years after surgery, despite being subjected to pre- and post-surgery chemotherapy regimes. Thus, specific biomarkers to target aggressive cell phenotypes and direct molecular-based therapy are warranted. Recently, evidences have been presented that advanced stage bladder cancers express the cell-surface tumor-associated carbohydrate antigen sialyl-Tn (STn), which may be used to target aggressive bladder cancer cells. The STn antigen results from a premature stop in the O-glycosylation of cell-surface proteins and has been found to prevent immune recognition, contributing to avoid metastatic cell elimination, modulates the malignant phenotype and enhances the metastatic ability of cancer cells. In the present study, a series of 96 patients with bladder cancer of different stages was screened for STn expression and proliferation (over-expression of Ki-67) by immunohistochemistry. This showed an association between STn expression and tumor proliferation and invasion. STn expression was also observed in lymph node and distant metastases of STn positive tumors. The STn antigen was mainly detected in high-molecular weight glycoproteins (>250 kDa) and low-molecular weight proteins at 25, 15 and 10 kDa. These low-molecular weight species predominated in lymph node mestastasis samples that also did not present high-molecular weight proteins, suggesting a molecular signature associated with metastasis. Altogether, the STn antigen presents potential for the development of new therapies against aggressive bladder cancer. Studies should be conducted to determine the nature of the STn-expressing glycoproteins and disclosing the possibility of a molecular signature associated with metastasis. The second part of the work focused on the validation of a STn-expressing bladder cancer xenograft as a model to drug testing and identification of prognostic biomarkers. A STn-positive muscle-invasive bladder tumor and its first, second and third generation xenotransplants were compared in relation to proliferation (Ki-67), differentiation (p63 and CK20), aggressiveness (p53) and STn expression, by immunohistochemistry. Histological and histochemical expression patterns were similar between primary tumor and xenografts, highlighting a degree of similarity between the animal model and the human tumor. However, p53 and Ki-67 levels increased along passages while STn decreased, suggesting a selection of the most proliferative clones. The generated information is regarded of primary importance to expand the knowledge about the clinical relevance of STn in bladder cancer and create the rationale for a STn-based therapy.